Determinan Belanja Desa di Kecamatan Ponggok Kabupaten Blitar Tahun 2019-2021 - Mita Putri Lestari; Nur Diana; Umi Nandiroh (Universitas Islam Malang, 2023)
The background of this research is the increase and decrease in village spending in various villages that occurred in the 2019-2021 period. The increase and decrease in village spending that occurs will affect village income, village spending is mostly financed by village fund allocations, village funds and village original income so that in this study it is formulated whether village fund allocations, village funds and village original income affect village spending. This study aims to determine the effect of village fund allocation, village funds and village original income on village spending in Ponggok District. The method used in this study is the correlational method. The data used in this study is secondary data in the form of village financial reports issued by Ponggok District for the 2019-2021 period and collected using the documentation method. Data analysis used descriptive statistical test, multiple linear regression analysis, normality test, classical assumption test and hypothesis test. The results of this research show that village fund allocations, village funds and village original income affect village spending in Ponggok District in 2019-2021.Keywords: Allocation of village funds, village funds, village original income, village expenditures